The Right to Development versus Environmental Protection: With Special Reference to the Malaysian Federal Constitution - Masum, Ahmad (American Scientific Publishers, 2017)
The right to development is aimed at improving the quality of life and living conditions of ordinary people. On the other hand, the right to the environment has as its purpose the conservation and prudent utilisation of natural resources. Theoretically, the two rights are at loggerheads. However, at the centre of these rights is the concept of sustainable development which harmonises the implementation of developmental activities and environmental protection. The paper aims to examine the relationship between the right to development and the right to the environment by way of making reference to the Malaysian Federal Constitution. This paper adopts a legal library research methodology focusing mainly on primary and secondary legal sources. The paper argues that although there are no express constitutional provisions under the Malaysian Federal Constitution addressing these two rights, public participation is vital as it ensures that the public is well informed about development projects that may have adverse effects on the environment. Generally, the developed nations have inculcated the need for environmental sustenance into economic development plans while developing countries are yet to imbibe it in practice even when expressly stated in their national legislations and policies. The paper reveals that Malaysia is still faced with the problem of competing demands of greater urban development and conserving the environment. The commitment to integrate environment and economic policies at present is slightly hesitant owing to a misunderstood concept that preservation of environment means limited development. Malaysia has to adopt a balanced approach in dealing with these two rights instead of giving preference to economic development.